Does rule of law support the capital market?. Issue 1 (1st January 2018) - Dima, Bogdan; Barna, Flavia; Nachescu, Miruna-Lucia
Abstract: By using data for 45 countries, for a time span between 2009 and 2014, the present paper supports the thesis of a positive and significant correlation between the rule of law and capital market development. In order to achieve this goal, the Rule of Law variable reported by Worldwide Governance Indicators is considered. The relationship remains robust even if control variables such as other legal system variables, including protection of minority investors, enforcing contracts or strength of legal rights of borrowers and lenders as well as initial levels of market development, economic growth, market liquidity, domestic credit to private sector and foreign direct investments are considered.